Penerapan Model Problem Based Learning Berbasis Teams Games Tournament untuk Meningkatkan Sikap Gotong Royong dan Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila Kelas VI SD Negeri Kleco 1 Surakarta - Salsabila, Irfina; Novitasari, Meggy; Stiyani, Dwi Fuji My (FONDATIA, 2024)
This study is an action research triggered by the absence of a spirit of cooperation among students during the learning process in class VI of SD Negeri Kleco 1 Surakarta. Its focus is to explore the impact of implementing a problem-based learning model with team games tournaments on enhancing students' cooperative attitudes and learning achievements. Conducted in class VI D of SDN Kleco 1 Surakarta in the first semester of the academic year 2023/2024 with the participation of 27 students, this research was carried out in two phases. Data collection utilized observation, tests, and documentation methods, with analysis combining qualitative and quantitative approaches. The results indicated that during the pre-cycle stage, students' cooperative attitudes were not observed (0%), with a learning achievement rate of 29.62%. However, in Cycle I, there was a significant improvement, with cooperative attitudes reaching 33% and learning achievement increasing to 59.25%. Cycle II showed further improvement, with cooperative attitudes reaching 63% and learning achievement reaching 100%. This improvement signifies the success of the learning model in enhancing students' cooperative attitudes and learning achievements. In conclusion, the application of problem-based learning (PBL) with teams games tournaments (TGT) can effectively enhance students' cooperative attitudes and learning achievements.